Advancing Fundraising. - Fundraising Institute Australia (Chatswood, N. S. W. : Fundraising Institute Australia, 2009)
The magazine for members of the national peak body for professional fundraising in Australia.
Title from cover.
Description based on: Issue 6 (May/June 2010).
Also available in an electronic version via the Internet. Address as at 22 June 2010: http://www.fia.org.au/Content/NavigationMenu/FIAPublications/AdvancingFundraising/default.htm
Keywords: Fundraising Institute Australia -- Periodicals; Fund raising -- Australia -- Periodicals